Punto de partida : apuntes para una coleccion. (Sevilla : CAAC (Centro Andaluz de Arte Contemporaneo), 2000)
Agredano, Rafael ; Badiola, Txomin ; Barbadillo, Manuel ; Bermejo, José Maria ; Bleckner, Ross ; Bourgeois, Louise ; Brossa, Joan ; Burguillos, Jaime ; Cabrera, Patricio ; Campo, Salomé del ; Carrasco, Nuria ; Cobo, Chema ; Delgado, Gerardo ; Dokoupil, Jiri Georg ; Equipo 57 ; Espaliú, Pepe ; Gil, Alonso ; Gil, Victoria ; Gonzalez, Curro ; Gordillo, Luis ; Guerrero, José ; Guzman, Federico ; Horn, Rebecca ; Isidro, Juan Francisco ; Ivars, Joaquin ; Kosuth, Joseph ; Lacalle, Abraham ; Lacomba, Juan F. ; Lasker, Jonathan ; López Cuenca, Rogelio ; Marin, Jesús ; Mendieta, Ana ; Millarès, Manuel ; Mora, Pedro ; Moraza, Juan Luis ; Palazuela, Pablo ; Paneque, Guillermo ; Peinado, Francisco ; Perez Siquier, Carlos ; Pérez Villalta, Guillermo ; Pérez, Marta Maria ; Puch, Gonzalo ; Romero, Pedro G. ; Rubio, Pepa ; Rueda, Gerardo ; Salinas, Manuel ; Schlosser, Adolf ; Serrano, Andres ; Sicilia, José Maria ; Sierra, José Ramon ; Sosa, Antonio ; Soto, José ; Suarez, Juan ; Tovar, Ignacio ; Uslé, Juan ; Viola, Bill ; Yturralde, Jose Maria ; Zobel, Fernando
Spaans
boek